Universal or Particular . or Both? The Right to Freedom of Religion or Belief in Cross-Cultural Perspective - Grüll, Christoph (The review of faith & international affairs, 2018)
The right to Freedom of Religion of Belief (FoRB) is a focus of increasing concern in academia and policy. A key disagreement is whether a universally recognized right to FoRB actually exists. This article explores this disagreement by considering global, universalist narratives and local, context-specific application of FoRB in India and Indonesia. We argue that the language of FoRB is not universal, but across different cultures, concepts and practices exist-such as honoring the traditions of others and living together in harmony-that are consistent with FoRB. Rather than insist on the language of FoRB, international actors should focus on these already existing practices.